USE OF PUBLIC RELATIONS INFORMATION TECHNOLOGY AT MAN INSAN CENDEKIA PASER: EFFICIENCY AND EFFECTIVENESS STUDY - Farihatun, Farihatun; Fajri, Muhamad; Sabran, Sabran; Yani, Khalif Oktifan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Public relations is a strategic aspect in strengthening the image of educational institutions, including MAN Insan Scholar Paser. However, public relations management often faces challenges related to the efficiency and effectiveness of information delivery. Information technology offers solutions to optimize this process through various applications and digital platforms. This research aims to analyze the use of information technology in public relations at MAN Insan Scholar Paser, with a focus on efficiency in the use of resources and effectiveness in reaching and satisfying stakeholders. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observations and document analysis, which were then analyzed descriptively. The research results show that the application of information technology in the public relations sector has increased efficiency, especially in terms of time and operational costs. The effectiveness of communication has also increased, as shown by increased stakeholder satisfaction and the achievement of public relations goals, such as the rapid and transparent dissemination of information. However, several technical obstacles and training needs are still challenges that need to be considered. This research confirms that information technology has a significant role in supporting the public relations function in educational institutions, as long as it is supported by adequate infrastructure and human resource capacity development